Leisure at work and employee flourishing. (20th October 2018) - Lacanienta, Andrew; Duerden, Mat D.; Widmer, Mark A.
Abstract: The purpose of this study was to examine the efficacy of Duerden, Courtright, and Widmer's leisure at work (LAW) model and explore the relationship between LAW and employee flourishing (i.e., resilience, work engagement, organizational identification). In a sample of 266 computer software employees, structural equation modeling revealed that LAW and leisure as a state of mind (i.e., intrinsic motivation, perceived freedom, positive affect) had positive relationships with personal expressiveness ( β = .704, p < .001) and organizational identification ( β = .164, p < .01). In addition, LAW had a positive relationship with resilience mediated by personal expressiveness ( β = .157, p < .01). Results suggest that LAW can provide added value to the workplace by facilitating personal expressiveness, resilience, and organizational identification. This study contributes to the discussion on LAW-related benefits and provides recommendations for practical application and future research.